Global evidence of positive impacts of freshwater biodiversity on fishery yields. Issue 5 (1st February 2016) - Brooks, Emma Grace Elizabeth; Holland, Robert Alan; Darwall, William Robert Thomas; Eigenbrod, Felix
Abstract: Aim: An often‐invoked benefit of high biodiversity is the provision of ecosystem services. However, evidence for this is largely based on data from small‐scale experimental studies of relationships between biodiversity and ecosystem function that may have little relevance to real‐world systems. Here, large‐scale biodiversity datasets are used to test the relationship between the yield of inland capture fisheries and species richness from 100 countries. Location: Inland waters of Africa, Europe and parts of Asia. Methods: A multimodel inference approach was used to assess inland fishery yields at the country level against species richness, waterside human population, area, elevation and various climatic variables, to determine the relative importance of species richness to fisheries yields compared with other major large‐scale drivers. Secondly, the mean decadal variation in fishery yields at the country level for 1981–2010 was regressed against species richness to assess if greater diversity reduces the variability in yields over time. Results: Despite a widespread reliance on targeting just a few species of fish, freshwater fish species richness is highly correlated with yield ( R 2 = 0.55) and remains an important and statistically significant predictor of yield once other macroecological drivers are controlled for. Freshwater richness also has a significant negative relationship with variability of yield over time in Africa ( R 2 = 0.16) but no effect in Europe. Main conclusions: The management of inland waters should incorporate the protection of freshwater biodiversity, particularly in countries with the highest‐yielding inland fisheries as these also tend to have high freshwater biodiversity. As these results suggest a link between biodiversity and stable, high‐yielding fisheries, an important win–win outcome may be possible for food security and conservation of freshwater ecosystems. However, findings also highlight the urgent need for more data to fully understand and monitor the contribution of biodiversity to inland fisheries globally.